Three-dimensional magnetohydrodynamic equilibrium of quiescent H-modes in tokamak systems. (11th May 2016) - Cooper, W A; Graves, J P; Duval, B P; Sauter, O; Faustin, J M; Kleiner, A; Lanthaler, S; Patten, H; Raghunathan, M; Tran, T-M; Chapman, I T; Ham, C J
Abstract: Three dimensional free boundary magnetohydrodynamic equilibria that recover saturated ideal kink/peeling structures are obtained numerically. Simulations that model the JET tokamak at fixed 〈 β 〉 = 1.7 % with a large edge bootstrap current that flattens the q -profile near the plasma boundary demonstrate that a radial parallel current density ribbon with a dominant m / n = 5/1 Fourier component at I t = 2.2 MA develops into a broadband spectrum when the toroidal current I t is increased to 2.5 MA.